NOM mitigates the phytotoxicity of AgNPs by regulating rice physiology, root cell wall components and root morphology. (May 2020) - Huang, Xitong; Li, Yong; Chen, Ke; Chen, Haiyan; Wang, Fei; Han, Xiaomin; Zhou, Beihai; Chen, Huilun; Yuan, Rongfang
Abstract: Natural organic matter (NOM) affects the environmental behaviors of AgNPs, which may change their phytotoxicity to plants. However, more evidence can be provided to illustrate how NOM influences AgNPs-induced phytotoxicity. In this study, using rice ( Oryza sativa ) as a model, the effects of NOM, Suwannee River humic acid (SRHA) and fulvic acid (FA), on the dissolution and phytotoxicity of AgNPs were investigated. Silver ions decreased in both AgNPs and AgNO3 solution in the presence of NOM, and the effect of SRHA was stronger than FA. Image-XRF (iXRF) results showed that Ag mainly remained in the root rather than the shoot of rice seedling exposed to AgNPs. NOM mitigated the negative effects of AgNPs and AgNO3 on rice with lower germination inhibition rate, less chlorophyll reduction, more relative biomass and less O2 − content. Moreover, NOM improved root cell viability according to FDA fluorescent dye as well as maintained the normal root morphology. Interestingly, the neutral sugars content from pectin, hemicellulose 1, hemicellulose 2 and cellulose of root cell wall in AgNPs and AgNO3 treatments differed from the control, while it was close to the regular content in AgNPs/AgNO3 +SRHA/FA groups, which implied that NOM regulated the changes. Besides, SRHA led to less germination and less relative biomass than FA due to different chemical characters. Thus, NOM needs to be considered when studying the phytotoxicity of AgNPs. Graphical abstract: Image 1 Highlights: Natural organic matter decreased the free Ag + in AgNPs and Ag + solution. Natural organic matter tried to retain the regular polysaccharides content of root cell wall by interacting with AgNPs. Chemical action between natural organic matter and AgNPs maintained the normal morphology of AgNPs-exposed root. Abstract : NOM regulate the responses of root morphology and polysaccharide to the stress of AgNPs.